Acute changes in acceleration phase sprint biomechanics with lower body wearable resistance - Simperingham, K. D.; Cronin, J. B.; Ross, A.; Brown, S. R.; Macadam, P.; Pearson, S. (Sports Biomechanics, 2022)
The aim of this acute cross-sectional study was to quantify the kinematic and kinetic changes that occur during sprint acceleration when lower body WR is worn. Fifteen male rugby athletes (19 years; 181 cm; 91 kg) were assessed during maximal effort over-ground and treadmill sprinting over 20 m under three different loading conditions: 0%, 3% and 5% body mass (BM) added weight attached to the lower body. Treadmill data provided a convenient estimate of kinetic changes in the absence of in-ground force plates. The loaded conditions resulted in significantly increased ground contact time (5 to 6%) and decreased step frequency (-2 to -3%) during sprint accelerations (effect size = 0.32-0.72). Moderate WR loading (3% BM) resulted in increased (9%; effect size = 0.66) theoretical maximum horizontal force (relative to BM) and unchanged 20 m sprint times (p > 0.05). Heavier WR loading (5% BM) resulted in a significant decrease (-4%) in vertical ground reaction forces (relative to total system mass) and slower (1 to 2%) 20 m sprint times (effect size = 0.38-0.70). Lower body WR loading up to 5% BM can provide specific sprint training overload, while affecting sprint acceleration biomechanics by = 6%.